2015
DOI: 10.3390/s150923286
|View full text |Cite
|
Sign up to set email alerts
|

INS/GPS/LiDAR Integrated Navigation System for Urban and Indoor Environments Using Hybrid Scan Matching Algorithm

Abstract: This paper takes advantage of the complementary characteristics of Global Positioning System (GPS) and Light Detection and Ranging (LiDAR) to provide periodic corrections to Inertial Navigation System (INS) alternatively in different environmental conditions. In open sky, where GPS signals are available and LiDAR measurements are sparse, GPS is integrated with INS. Meanwhile, in confined outdoor environments and indoors, where GPS is unreliable or unavailable and LiDAR measurements are rich, LiDAR replaces GPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 27 publications
0
90
0
Order By: Relevance
“…A Strap-down Inertial Navigation System (SINS) estimates the position, velocity and attitude by integrating the IMU data. In this paper, we choose east-north-up (ENU) as the navigation reference frame (n), and right-forward-up (RFU) as the body frame (b) [5], and we also use the earth frame (e) and the inertial frame (i) [29]. Primarily, the differential equation [5] [29] [1] in n frame of SINS is well known as:…”
Section: A Sins Kinematics Equation and Error Equationmentioning
confidence: 99%
“…A Strap-down Inertial Navigation System (SINS) estimates the position, velocity and attitude by integrating the IMU data. In this paper, we choose east-north-up (ENU) as the navigation reference frame (n), and right-forward-up (RFU) as the body frame (b) [5], and we also use the earth frame (e) and the inertial frame (i) [29]. Primarily, the differential equation [5] [29] [1] in n frame of SINS is well known as:…”
Section: A Sins Kinematics Equation and Error Equationmentioning
confidence: 99%
“…However, GPS/INS is still subject to growing drift and biases in long periods of GPS outages or degraded GPS. Environment observing sensors such as the LiDAR sensor have been used to generate odometry measurements by measuring changes in the observed environment. Dill et al have shown that integrating LiDAR with INS is able to obtain global anchor navigation solutions to meter‐accuracy when GPS is available .…”
Section: Related Workmentioning
confidence: 99%
“…By incorporating GPS, the positions and maps generated by the SLAM algorithms are anchored to the global frame . Gao et al implemented fusion of INS/GPS/LiDAR measurements for urban and indoor navigation using a hybrid scan matching algorithm . Shepard et al implemented a navigation system combining Parallel Tracking and Mapping (PTAM) processed camera measurements with carrier‐phase differential GPS …”
Section: Related Workmentioning
confidence: 99%
“…On the one hand, the integrated corridor is built underground, with only a small number of feeding ports, personnel entrances and exits [1]. In the actual operation process, it may cause a blind spot, or even form a blind zone, becoming an accident-prone zone.…”
Section: Introductionmentioning
confidence: 99%